1968
DOI: 10.1007/bf00148082
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields and the temperature structure of the chromosphere-corona interface

Abstract: The temperature structure of the transition region between the chromosphere and corona is discussed in the context of current ideas about magnetic fields in these layers. Magnetic channeling of the downward conductive heat flow from the corona into the regions of enhanced field at the supergranulation boundaries is proposed as a mechanism for explaining the measured intensities of solar ultraviolet emission lines which originate in layers with temperatures below 105 ~ It is shown that nearly all of the observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(26 citation statements)
references
References 9 publications
2
23
1
Order By: Relevance
“…Generally the highest filtered continuum intensity (thin black contours) are associated with high magnetic field concentrations. This can be expected since the relation between bright network patches and magnetic field concentration has been known since Kopp & Kuperus (1968). However these network patches do not necessarily coincide with the brightest regions in line intensity and not even necessarily with the brightest regions in the continuum image (upper left panel in Fig.…”
Section: Coronal Outflowsmentioning
confidence: 87%
See 1 more Smart Citation
“…Generally the highest filtered continuum intensity (thin black contours) are associated with high magnetic field concentrations. This can be expected since the relation between bright network patches and magnetic field concentration has been known since Kopp & Kuperus (1968). However these network patches do not necessarily coincide with the brightest regions in line intensity and not even necessarily with the brightest regions in the continuum image (upper left panel in Fig.…”
Section: Coronal Outflowsmentioning
confidence: 87%
“…In this context the role of the magnetic field for intensity enhancements and in velocity variations is still not clear. Kopp & Kuperus (1968) first proposed an enhanced magnetic field as a reason for the measured intensity enhancement of UV emission lines in the temperature regime below 10 5 K. Later Reeves et al (1974) observed that in lines formed above 10 5 K the network structure disappears. Based on this, Gabriel (1976) developed a model relating the observed bright EUV network to magnetic flux concentrated at supergranular boundaries of the convective flows at the chromospheric level.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, there are various other numerous proposed physical processes responsible for the formation of spicules. Among others, the compression of the plasma sheet by the magnetic field (Hollweg 1972), Joule heating in the current sheet (Hirayama 1992), thermal conduction from the corona (Kopp & Kuperus 1968;Moore & Fung 1972) and buffeting of anchored magnetic flux by granulation can lead to spicules (Roberts 1979). These and various other mechanisms are discussed by Sterling (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature gradient near the Sun is determined by processes occurring in the lower corona where heat conduction into the chromosphere is very important (Kuperus and .Athays (12) 1967; Kopp and Kuperus, 1968;Kuperus, 1969). In order to proceed without becoming involved in the complexities of the chromospherecorona interface, we will assume that the coronal temperature distribution is spherically symmetric near the Sun, and that the temperature gradient is given by Equation (6) far all heliolatitudes (cf.…”
Section: Governing Equationsmentioning
confidence: 99%